RUSSIA AND CHINA: THE MAIN AREAS OF DEVIANCE AT THE BEGINNING OF THE XXI CENTURY - S. Yanli; M. Romanenko (Вестник университета, 2017)
The article analyses the main forms of deviance in modern Russia and in modern China. Found that media of deviant behavior, both in Russia and in China, are recruited from all segments of society. It was revealed that on threats, social urgency and magnitude of the manifestations of the first place both in Russia and in China took the crime, followed by alcoholism, drug abuse, suicide, corruption. There are two opposing trends in the evolution of deviance: in Russia there is in General a spontaneous escalation of deviance in China-minimization of deviance, mixing its manifestations. This article is useful for establishing an effective social control over deviant processes with a view to their elimination.